Indirect treatment comparison of bevacizumab + interferon-α-2a vs tyrosine kinase inhibitors in first-line metastatic renal cell carcinoma therapy - Gerald HJ Mickisch; Björn Schwander; Bernard Escudier; et al (Dove Medical Press, 2011)
Gerald HJ Mickisch1, Björn Schwander2, Bernard Escudier3, Joaquim Bellmunt4, José P Maroto5, Camillo Porta6, Stefan Walzer7, Uwe Siebert8,91Department of Urology, Center of Operative Urology Bremen, Bremen, Germany; 2Department of Outcomes Research, AiM GmbH Assessment-in-Medicine, Lörrach, Germany; 3Immunotherapy Unit, Institut Gustave Roussy, Villejuif, France; 4Department of Medical Oncology, University Hospital del Mar UPF, Barcelona, Spain; 5Department of Medical Oncology, Hospital de la Santa Creu i Sant Pau, Barcelona, Spain; 6Department of Medical Oncology, IRCCS San Matteo University Hospital Foundation, Pavia, Italy; 7Global Health Economics, F Hoffmann-La Roche Pharmaceuticals AG, Basel, Switzerland; 8Department of Public Health, Medical Decision Making and Health Technology Assessment, UMIT - University for Health Sciences, Medical Informatics and Technology, Hall i.T., Austria; 9Department of Health Policy and Management, Harvard School of Public Health, Boston, MA, USABackground: The vascular endothelial growth factor inhibitor bevacizumab (BEV) given in combination with interferon-α-2a (IFN), and the tyrosine kinase inhibitors (TKIs) sunitinib (SUN) and pazopanib (PAZ), have all shown significant increase in progression-free survival (PFS) in first-line metastatic renal-cell carcinoma (mRCC) therapy. These targeted therapies are currently competing to be primary choice; hence, in the absence of direct head-to-head comparison, there is a need for valid indirect comparison assessment.Methods: Standard indirect comparison methods were applied to independent review PFS data of the pivotal Phase III trials, to determine indirect treatment comparison hazard-ratios (HR) with 95% confidence intervals (95% CI). As BEV+IFN and SUN have been compared to IFN, indirect comparison was enabled by the common IFN comparator arms. As PAZ was compared to placebo (PLA), a connector trial (IFN vs PLA) was required for the indirect comparison to BEV+IFN. Sensitivity analyses taking into account real-life influence of patient compliance on clinical outcomes were performed.Results: The indirect efficacy comparison resulted in a statistically nonsignificant PFS difference of BEV+IFN vs SUN (HR: 1.06; 95% CI: 0.78–1.45; P = 0.73) and of BEV+IFN vs PAZ (range based on different connector trials; HR: 0.74–1.03; P = 0.34–0.92). Simulating real-life patient compliance and its effectiveness impact showed an increased tendency towards BEV+IFN without reaching statistical significance.Conclusions: There is no statistically significant PFS difference between BEV+IFN and TKIs in first-line mRCC. These findings imply that additional treatment decision criteria such as tolerability and therapy sequencing need to be considered to guide treatment decisions.Keywords: indirect treatment comparison, progression-free survival, renal cell carcinoma, bevacizumab, sunitinib, pazopanib